Analysis of muscle damage and strength in training and competition simulation in brazilian jiu jitsu athletes - Fonseca, L. B.; Aidar, F. J.; de Matos, D. G.; de Almeida Barros, N.; de Souza, R. F.; Oliveira, A. S.; dos Santos, J. L.; de Araujo Tinoco Cabral, B. G.; Marcal, A. C.; Reis, V. M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. It is important to evaluate the specificity of the training and its relationship with the competition variables in Jiu Jitsu athletes. Problem and aim. The objective was to analyze muscle damage, strength, and their correlation under two distinct conditions, a specific training session and a competition simulation session. Methods. The study sample included nine subjects (22.50±2.84 years) that were submitted to the following two interventions: 1. simulation of training and 2. simulation of competition. Results: It can be observed that there were no significant differences in the Counter Movement Jump (CMJ) test; however, 48 h after training, higher values than those in the week of the competition were observed. Regarding Creatine Quinase (CK) levels, there were significant differences after competition in relation to the other time points and the intervention (p=0.004), with a high effect. The Lactate Dehydrogenase (LDH) levels, there were significant differences in post-competition and pre-competition in relation to pre- and post-training (p=0.019), with a high effect. It was observed that the power in the upper limbs (PUL) results showed a median correlation 24 (0.554) and 48h (0.473) after the intervention. The Squat Jump (SJ) test results showed a high cor- relation (0.716), and the other test results showed a very high correlation (>0.8). All variables presented a very high correlation at both time points of the study. Only the variable LDH level, 48 h later, presented a high correlation. Conclusion. It was concluded that a good correlation exists between training simulation and competition simulation, where the model adopted as training can meet the needs imposed in the competition.